Renewing Trust through Inclusion: Rethinking Leadership in the South African Police Service - (:unkn) unknown (My University, 2025)
Background: For decades, the legacy of the past has cast a shadow, creating a disconnect between the diverse communities the South African Police Service (SAPS) serves and the officers who patrol their streets. By fostering a culture of inclusion, the SAPS can not only reflect the vibrant tapestry of South Africa but also leverage the power of diverse perspectives to build stronger relationships with the public, make better decisions, and ultimately, create a safer nation for all. Here, a historical background, emphasising apartheid's legacy and how it affected the SAPS's connection with the community, has been given. The purpose of this chapter is to shed light on the value and possibilities of inclusive leadership in the South African Police Service (SAPS).Problem Synopsis: The main obstacles to developing inclusive leadership include prejudice that isn't conscious, a lack of education, and mistrust from the past. By fostering a more inclusive environment, SAPS can strengthen its relationship with the community, improve policing strategies, and create a more positive and productive work environment for its officers.Methodological Approach: Although not a research study, the article will cite reliable sources to bolster its claims, including reports, studies, and expert comments.Key Takeaways/Results: The paper makes the case that inclusive leadership builds community trust and is necessary for efficient law enforcement. It will showcase research results that bolster this claim, like higher officer morale and better problem-solving through a variety of viewpoints. Several studies explore the positive outcomes associated with inclusive leadership in police forces. A study demonstrated how a diverse leadership team can lead to improved decision-making and problem-solving within the police force. Similarly, another study highlighted the link between inclusive leadership, employee satisfaction, and trust within police organisations. These findings suggest
Keywords: African Research